Effectivity of Langsa City Regional Asset Management - Iqlima Azhar; Raihan Aditya Perkasa; Agustina Nurul Fajriah; Nurliza Lubis (Akbis: Media Riset Akuntansi dan Bisnis, 2026)
The purpose of this study is to investigate the impact of human resource competency, internal control systems, and information systems on the effectiveness of regional asset management in Langsa City Regional Apparatus Organizations (OPDs). This study employs a quantitative approach, with primary data acquired via the distribution of OPD questionnaires chosen using a purposive sampling procedure. Data were evaluated using the IBM SPSS Statistics 25 application, which included descriptive statistics, validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The study's findings show that human resource competency, internal control systems, and information systems all have a major impact on the success of regional asset management. Furthermore, these three variables have a major impact on the success of regional asset management. The coefficient of determination value indicates that 54.2% of the efficacy of regional asset management is influenced by human resource competency, internal control systems, and information systems, with the remaining influenced by elements beyond the scope of this study. This study's findings show that enhancing apparatus competency, strengthening internal control mechanisms, and optimizing information systems can improve the transparency, accountability, and efficiency of regional asset management.